Juvenile granulosa cell tumor in a 35-year-old pregnant woman: A rare case report - Sharma, Jagannath D; Kalita, Upasana; Deka, Muktanjalee; Bharadwaj, Barasha; Beso, Adahra Patriesa (Indian Journal of Case Reports, 2024)
Juvenile granulosa cell tumors (JGCTs) account for 5% of GCT and 3% are diagnosed after 30 years of age. JGCT is an uncommon neoplasm in pregnancy. About 90% are stage I at diagnosis but advanced-stage tumors are aggressive often resulting in recurrence or death within 3 years of diagnosis. We present a case of JGCT in a pregnant woman of 35 years old. The patient complained of sudden onset pain in her second trimester. Ultrasound whole abdomen was done and a malignant lesion was detected. Subsequently, the left ovarian cystectomy was performed and a diagnosis of JGCT was given which was confirmed by histopathology and immunohistochemistry.